Assessment on tracking error performance of Cascade P/PI, NPID and N-Cascade controller for precise positioning of xy table ballscrew drive system - Abdullah, Lokman; Jamaludin, Zamberi; RAFAN, NUR AIDAWATY; Jamaludin, Jailani; Tsung Heng, Chiew (2013)
Abstract. At present, positioning plants in machine tools are looking for high degree of accuracy and robustness attributes for the purpose of compensating various disturbance forces. The objective of this paper is to assess the tracking performance of Cascade P/PI, Nonlinear PID (NPID) and Nonlinear cascade (N-Cascade) controller with the existence of disturbance forces in the form of cutting forces. Cutting force characteristics at different cutting parameters; such as spindle speed rotations is analysed using Fast Fourier Transform. The tracking performance of a Nonlinear cascade controller in presence of these cutting forces is compared with NPID controller and Cascade P/PI controller. Robustness of these controllers in compensating different cutting characteristics is compared based on reduction in the amplitudes of cutting force harmonics using Fast Fourier Transform. It is found that the Ncascade controller performs better than both NPID controller and Cascade P/PI controller. The average percentage error reduction between N-cascade controller and Cascade P/PI controller is about 65 % whereas the average percentage error reduction between cascade controller and NPID controller is about 82 % at spindle speed of 3000 rpm spindle speed rotation. The finalized design of N-cascade controller could be utilized further for machining application such as milling process. The implementation of N-cascade in machine tools applications will increase the quality of the end product and the productivity in industry by saving the machining time. It is suggested that the range of the spindle speed could be made wider to accommodate the needs for high speed machining. .